THE ANALYSIS OF SUNDANESE LANGUAGE TO STUDENTS' ENGLISH CONSONANT PRONUNCIATION CONDUCTED IN SMA MUTIARA PALABUHAN RATU - Anisa Alawiyyah; Handi Pabriana (Dialectical Literature and Educational Journal, 2020)
In this modern era, we are forced to be able to communicate with people around the world. Communication related with language that every country has their language. English as most spoken English in the world made it become an international language. Learning English as foreign language has many problem especially with their mother tongue. The connection of both language is influence each other especially English. For sure Sundanese as the second most spoken language in Indonesia. Many Sundanese native learnt English especially students. The different structure both of language was influenced especially the consonant differences The relation between English and Sundanese is in their different structure of consonants sound especially in the pronunciation both of languages. This research has aims to know the main appearances of Sundanese language to student English consonant pronunciation, fricative English sounds pronounced by Sundanese student, and new variant that appear in student English consonant pronunciation. This research used descriptive qualitative research as the method of the research. The instruments of this research are questionnaire, test and interview which are conducted to 42 samples of SMA Mutiara Terpadu Palabuhanratu. This research found that 100% sample transformed the sound ð to d or t, 100% sample transformed the sound ‘?’ to ‘s’, 100% sample transformed ‘?’ to ‘c’, 96% sample transformed the sound ? to d or g, 98% sample transformed ? to ‘s’, 94% samples transformed ‘f’ to ‘p’, 100% samples transformed sound ‘v’ to ‘f’ or ‘p’, 100% samples transformed sound ‘?’ to ‘t’, and 100% samples transformed ‘z’ to ‘s’ to ‘j’. Beside that, the double consonant in a word was banned, such as: ‘around’ to ‘aroun’, and ‘almost’ to ‘almos’. The conclusion of this research is the unknown consonant of Sundanese in English transformed to Sundanese similar sound, and the rule of English pronunciation was equalized with Sundanese rules.